Total Synthesis and Potential Bioactivity of Linear Peptide LSAVTPG - Anderson Arnold Aloanis; Vlagia Indira Paat; Suleman Duengo (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
The total synthesis of the linear peptide LSAVTPG was successfully carried out using the solid-phase peptide synthesis (SPPS) method. The synthesis employed the Fmoc/tBu protection strategy on a 2-chlorotrityl chloride resin as the solid support. Following chain assembly, the final peptide was cleaved from the resin using 95% trifluoroacetic acid (TFA), affording the target peptide with a yield of 81.6%. Structural confirmation was performed by high-resolution mass spectrometry (HRMS), which showed an observed ion at m/z 644.3621, consistent with the calculated value of m/z 644.3619 for C₂₈H₅₀N₇O₁₀. Purity and retention characteristics were further analyzed using analytical HPLC, where the peptide exhibited a retention time of 13.536 minutes. These results demonstrate that the SPPS method with Fmoc/tBu chemistry is an efficient strategy for the synthesis of the LSAVTPG peptide with high yield and analytical confirmation. The potential bioactivity screened computationally and showed some potential such as spanning oncology, cardiometabolic regulation, neurodegeneration, immunology, and inflammation.